(untitled) (Journal of Oriental Studies, 2016)
The aim of this paper is to investigate a process of modernization of the People’s Republic of China. With the separation the stages of modernization in China, the author shows the evolution of the process in these countries. The author is also considered the current modernization and reforms that are taking place in China.